Iasonos, Iasonas - (:unkn) unknown (My University, 2026)
Iasonas (Jason) Aliferis is a Graduate Officer of the Hellenic Fire Academy and holds a Degree in Statistics and Insurance Science (University of Piraeus). His postgraduate studies in Environmental, Disaster, and Crisis Management Strategies with a specialization in Governance, combined with his research experience as a Ph.D. Candidate in the integration of Innovative Technologies in Disaster Management (University of Athens), have been utilized for several years by the National Coordinating Center for Operations and Crisis Management of the Hellenic Fire Corps. Furthermore, he is part of the National Representative team of the Hellenic Fire Corps at the International Association of Fire Services Scientific Advisory Group. As an Officer, he is also an experienced UAS Pilot and Instructor. Iasonas is certified in related domains by NATO, EUROCONTROL, UN, HNDGS, HCAA, EASA, and ESA. Additionally, he has experience not only as a Researcher in five Research Projects, four of which are European-funded, but also works as a freelancer in the field of IT Consulting and Analysis.